Malpractice claimed calls within the Swedish Healthcare Direct: a descriptive - comparative case study - Annica Björkman; Maria Engström; Ulrika Winblad; Inger K. Holmström (BMC, 2021)
Abstract Background Medical errors are reported as a malpractice claim, and it is of uttermost importance to learn from the errors to enhance patient safety. The Swedish national telephone helpline SHD is staffed by registered nurses; its aim is to provide qualified healthcare advice for all residents of Sweden; it handles normally about 5 million calls annually. The ongoing Covid-19 pandemic have increased call volume with approximate 30%. The aim of the present study was twofold: to describe all malpractice claims and healthcare providers' reported measures regarding calls to Swedish Healthcare Direct (SHD) during the period January 2011-December 2018 and to compare these findings with results from a previous study covering the period January 2003-December 2010. Methods The study used a descriptive, retrospective and comparative design. A total sample of all reported malpractice claims regarding calls to SHD (n = 35) made during the period 2011-2018 was retrieved. Data were analysed and compared with all reported medical errors during the period 2003-2010 (n = 33). Results Telephone nurses' failure to follow the computerized decision support system (CDSS) (n = 18) was identified as the main reason for error during the period 2011-2018, while failure to listen to the caller (n = 12) was the main reason during the period 2003-2010. Staff education (n = 21) and listening to one's own calls (n = 16) were the most common measures taken within the organization during the period 2011-2018, compared to discussion in work groups (n = 13) during the period 2003-2010. Conclusion The proportion of malpractice claims in relation to all patient contacts to SHD is still very low; it seems that only the most severe patient injuries are reported. The fact that telephone nurses' failure to follow the CDSS is the most common reason for error is notable, as SHD and healthcare organizations stress the importance of using the CDSS to enhance patient safety. The healthcare organizations seem to have adopted a more systematic approach to handling malpractice claims regarding calls, e.g., allowing telephone nurses to listen to their own calls instead of having discussions in work groups in response to events. This enables nurses to understand the latent factors contributing to error and provides a learning opportunity.